Translation and Validation of the Italian Version of the Spiritual Care Competence Questionnaire (SCCQ) - Singh Solorzano, Claudio (Journal of religion and health, 2026)
Despite the growing interest in spirituality within healthcare, specific instruments are needed to measure healthcare professionals’ spiritual care competencies as a first step toward improving them. This study translates the Spiritual Care Competence Questionnaire (SCCQ) into Italian and validates it in a sample of 494 healthcare professionals recruited via a 15-min online survey across 14 health and care centers. To enable cross-validation, the dataset was randomly split 60/40 into EFA and CFA sets; to mitigate item non-response, missing data were addressed via multiple imputation. Exploratory factor analysis supported a 17-item, four-factor solution explaining 38% of variance, with good internal consistency (α = 0.78-0.87) and modest inter-factor correlations (r = 0.23-0.42). Using the independent subsample (n = 198), confirmatory factor analysis corroborated this structure with acceptable fit and significant loadings. Taken together, the Italian SCCQ shows sound psychometric properties and may serve to assess spiritual care competencies, guide educational planning for healthcare professionals, and monitor improvements over time. Future work should combine qualitative and quantitative approaches and extend validation across diverse samples and settings to strengthen the evidence base for integrating spirituality into healthcare practice.